Hemodynamic load on the intracranial arterial system in subjects who have suffered a hemorrhagic stroke as a complication of essential arterial hypertension - Netiazhenko, V.Z.; Tkachyshyn , O.V. (Medicni Perspektivi, 2021)
The aim of the investigation was to compare a hemodynamic load on the intracranial arterial system, assessed by the indices of 24-hours ambulatory blood pressure monitoring and ultrasonography of the large cervical arteries between the group of patients with essential arterial hypertension in ≥6 months after a hemorrhagic stroke and a group of patients with essential arterial hypertension without complications. The first one was the main group (n=94; age – 54.4±0.9 years), М±m), the second one – the comparison group (n=104; age – 53.7±0.9 years). The indices of 24-hours ambulatory blood pressure monitoring in the main group and the comparison group were the following: the mean daytime systolic blood pressure was 109.6±1.6 and 121.1±1.1 mm Hg, the minimal one was 74.4±2.0 mm Hg and 82.3±12.5 mm Hg, and the maximal one was 168.2±1.9 and 161.9±1.7 mm Hg, p<0.05. The daytime systolic blood pressure sigma (17.9±0.6) and the average real variability of systolic blood pressure (11.31±2.52 mm Hg) were bigger in the main group (p<0.01). The daytime index of hyperbaric load of systolic blood pressure was bigger in the main group: it was 403.6±25.9 against 231.7±12.1 mm Hg × h in the comparison group (p<0.01). The maximal pulse pressure for a 24-hours interval was 74.2±2.0 and 66.4±0.9 mm Hg, respectively (p<0.01). The indices of ultrasonography of the large cervical arteries in the right and left vessels of the main group were the following: the Gosling’s pulsatility index was 1.578±0.059 and 1.552±0.042 for the common carotid artery, 1.210±0.044 and 1.102±0.037 for the internal carotid artery, 1.191±0.030 and 1.150±0.023 for the vertebral artery. The above-mentioned indices were bigger in the main group than in the comparison one (p<0.01). The diameters of all the large cervical arteries were bigger in the main group (p<0.01). Therefore, according to the above-mentioned indices which are associated with a bigger risk of cerebrovascular events, a bigger hemodynamic load on the intracranial arterial system was found in the main group than in the comparison one, despite the smaller mean systolic blood pressure indices.